Analysis of Changes in Environmental Awareness, Consumer Preferences and Zero-Waste Shopping on Green Consumer Behavior in the Millennial Generation in South Kalimantan - DEWI MAHARANI; Riyan Pradesyah; Khabib Musthofa (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the influence of changes in environmental awareness, consumer reference , and Zero-Waste Shopping on Green Consumer Behavior (GCB) in the millennial generation in South Kalimantan. The research method used is a quantitative approach with the Structural Equation Modeling (SEM) method. Data were collected through a questionnaire with a Likert scale and disseminated to 97 respondents who were selected using purposive sampling techniques.  The results showed that KL had a significant positive effect on GCB, while PK had no significant effect, indicating an attitude behavior gap. ZWS was the variable with the most dominant influence (β = 0.539; p 0.001) in forming GCB. Simultaneously, KL, PK, and ZWS accounted for 56.9% variation in GCB (R² = 0.569), indicating moderate predictive ability. The moderation analysis revealed that higher education strengthened the influence of KL, high income reduced behavioral barriers to PK, and more mature millennials strengthened the consistency of ZWS implementation. The implications of this research are expected to contribute to the community by educating the public in increasing awareness of a more sustainable lifestyle by encouraging green marketing strategies, government policies that support an environmentally friendly lifestyle for the environment. This research emphasizes that increasing sustainable consumption can be achieved through green marketing strategies, government policies that support environmentally friendly lifestyles, and consumer education about the impact of consumption on the environment.